Pengaruh Manajemen Keuangan dan Financial Technology Terhadap Kinerja Keuangan Umkm dengan Pengetahuan Keuangan sebagai Variabel Moderasi - Suyanto Suyanto; Haici Audi Aulia; Sri Ayem (Jurnal Literasi Akuntansi, 2026)
Purpose: This study aims to examine the influence of financial management and financial technology on the financial performance of MSMEs, with financial knowledge serving as a moderating variable. Method: The population in this study consists of all MSMEs registered in the Special Region of Yogyakarta (DIY). A total of 227 respondents were selected using purposive sampling. The research employed a quantitative approach through the distribution of questionnaires. The collected data were analyzed using multiple linear regression and processed with Eviews 12. Finding: The results show that financial management has a positive and significant effect on the financial performance of MSMEs, while financial technology has no significant effect. Financial knowledge positively moderates the relationship between financial management and financial performance but does not moderate the relationship between financial technology and financial performance. These findings indicate that financial management plays a crucial role in improving performance, whereas the use of financial technology has not yet provided optimal benefits due to its predominantly transactional use. Novelty: This study introduces financial knowledge as a moderating variable within the relationship between financial management, financial technology, and financial performance—an aspect that has been rarely examined. The focus on MSMEs in DIY that have adopted financial services offers a new context for understanding the effectiveness of financial management and the utilization of financial technology in enhancing MSME performance.